К ВОПРОСУ О СУЩНОСТИ И СООТНОШЕНИИ ПОНЯТИЙ «НАЦИОНАЛЬНАЯ БЕЗОПАСНОСТЬ» И «ГОСУДАРСТВЕННАЯ БЕЗОПАСНОСТЬ» - Якуб, Ирина (SUPREMANCE OF LAW, 2017)
The purpose of this article is to analyze the concepts of “national security” and “state security “, based on scientifi c research and legislation of the Republic of Moldova (National Security Concept of the Republic of Moldova, National Security Strategy of the Republic of Moldova, Law on State Security), to determine their nature and relations.
Keywords: security; national security; state security; threats; state; society; personality